Serum xanthine oxidase profile in stressed Marwari sheep from arid tracts in India - Maan R. (Journal of Stress Physiology & Biochemistry, 2012)
The present investigation was aimed to determine serum xanthine oxidase profile in stressed Marwari breed of sheep belonging to arid tracts in Rajasthan, India. Extreme hot and cold ambiences were considered as stress conditions to the animals. Blood samples were collected to obtain sera during moderate, extreme hot and cold ambiences. The mean value of serum xanthine oxidase during moderate ambience was 93.33±1.11 mU L-1.The mean value of serum xanthine oxidase was significantly (p≤0.05)higher during hot and significantly (p≤0.05) lower during cold ambiences as compared to moderate mean value serving as control. The sex and age effects were significant (p≤0.05) in all ambiences. The mean values were significantly (p≤0.05) higher in males than females. In each ambience the age effect showed a significant (p≤0.05) increase in the mean values being highest in the animals of 2.5-4.5 years of age. The effects of extreme ambiences were observed on the male and female animals of all age groups as revealed by various interactions studied viz. ambience X age; ambience X sex and age X sex (p≤0.01). Further sex effect was present in the animals of each age group. It can be concluded that serum xanthine oxidase can be used as an effective marker to assess oxidative stress in these animals. Mean values obtained from large number of animals during moderate ambience will help in providing physiological reference values for future research and clinical interpretations.